Effects of Mandatory Carbon Reporting on Greenwashing - Grewal, Jody; Richardson, Gordon; Wang, Jingjing (The Accounting Review, 2026)
ABSTRACT We study the effects of mandatory environmental reporting on greenwashing. Our setting is a regulation in the United Kingdom requiring firms to report carbon emissions, or mandatory carbon reporting (MCR). Measuring greenwashing as the discrepancy between companies’ external carbon-related discussions in corporate social responsibility (CSR) reports and their underlying carbon performance, we find MCR leads to a decline in three types of greenwashing: excessive length, over-optimism, and vague commitments, relative to performance. MCR also curtails greenwashing in other (noncarbon) environmental disclosures, suggesting a spillover from MCR to firms’ broader environmental reporting. Drivers are shown to include higher expected reputational and regulatory risks for noncarbon issues after MCR, and a governance spillover, where the governance resources allocated to MCR also benefit noncarbon reporting. Data Availability: Data are publicly available from sources indicated in the text. JEL Classifications: M41; Q56; G38; Q54.